Legacies. The complete third season. [videorecording (DVD)] - Russell, Danielle Rose; Shahghasemi, Aria; Bryant, Kaylee; Davis, Matthew, 1978- (Warner Bros., 2022)
As season three begins, Hope has risked everything to pull her friends back from the brink of a monstrous prophecy that threatened to doom them all. But when a heartbreaking loss shatters her whole world, Hope Mikaelson will be forced to fight fate itself.